Atributos mineralógicos e cinética da transformação térmica de Al-maghemitas (y-Fe2- xAlxO3) em Al-hernatitas (a-Fe2-xAlxO3) - Nonaka, Adriele Galeti (2013)
Maghemite (γ-Fe2O3) and hematite (α-Fe2O3) are important iron oxides in Brazilian soils derived from basalt. Maghemite can transform into hematite when exposed to high temperatures. However, isomorphic substitution (IS) (for example, Al³+) may largely influence this process. Iron oxides are the main pigment and magnetization agents in soils from tropical regions, where weathering is more intense and Al presence is common. We studied the kinetics of the thermal transformation from synthetic Al-maghemites into hematites, influenced by the presence of Al and time of exposition to heating. Maghemites with different degrees of Al-substitution (0.0, 1.0, 2.0, 2.9, 3.8, 5.6, 6.7, 10.0, 12.0 and 17.1 mol% Al) were submitted to the temperature of 500 ± 10°C for 0, 5, 10, 16, 64, 128, 192, 360, 720, 2160, 3600, 5040 and 6480 minutes. Samples were analyzed by X-rays Diffraction (XRD), Differential Thermal Analysis (DTA) and Scanning Electronic Microscopy (SEM). It was determined total Fe and Al contents and Fe and Al extracted by Mehlich-1 solution using Atomic Absorption Spectroscopy (AAS). Samples color were determined according to Munsell scale. Mass-specific magnetic susceptibility (χLF) and frequency-dependent mass-specific magnetic susceptibility (χFD) were also determined. X-rays diffractograms were analyzed by Rietveld refinement method and maghemite and hematite content were calculated by using the Rietveld refinement (1969) and the method proposed by Sidhu (1988). IS values obtained by AAS were higher than results published by the maghemites supplier. Obtained kinetics models by Rietveld refinement were better than the ones adjusted by Sidhu method. IS of Fe by Al increased critical temperature, the time necessary to the maghemite-to-hematite transformation, decreased lattice parameters and mean crystallite dimension (MCD) values to maghemite. To hematite, only c-dimension and MCD decreased with increasing Al-substitution. Available Fe content in Mehlich-1 to maghemites and hematites decreased with IS, whereas Al content increased. All analyzed samples presented hue YR. Hue proportion decreased with increasing heating time, and colors passed from brown to red. In a general way, the increasing IS led to increasing hue values from maghemite and hematite, and then, this last one became yellower. Samples χLF decreased, indicating the transformation of a ferrimagnetic phase (maghemite) to an antiferromagnetic (hematite). With increasing IS, maghemite χLF values decreased. χFD results did not show consistant behavior.